2022
DOI: 10.3390/ijms23073966
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Screening of 50 Curcumin Compounds as EGFR and NF-κB Inhibitors

Abstract: The improvement of cancer chemotherapy remains a major challenge, and thus new drugs are urgently required to develop new treatment regimes. Curcumin, a polyphenolic antioxidant derived from the rhizome of turmeric (Curcuma longa L.), has undergone extensive preclinical investigations and, thereby, displayed remarkable efficacy in vitro and in vivo against cancer and other disorders. However, pharmacological limitations of curcumin stimulated the synthesis of numerous novel curcumin analogs, which need to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 86 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…No. 12054-H09E, Sino Biological Europe GmbH, Eschborn, Germany), and the labeling was performed as previously described [ 53 ]. Serial dilutions from 300,000 to 100 nM of jozimine A 2 and michellamine B were incubated for 30 min at room temperature (RT) with the labeled human recombinant NF-κB protein in a 1:1 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…No. 12054-H09E, Sino Biological Europe GmbH, Eschborn, Germany), and the labeling was performed as previously described [ 53 ]. Serial dilutions from 300,000 to 100 nM of jozimine A 2 and michellamine B were incubated for 30 min at room temperature (RT) with the labeled human recombinant NF-κB protein in a 1:1 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…In their research, Mohamed EM Saeed and colleagues conducted a comprehensive molecular docking study involving 50 curcumin derivatives, sourced from the PubChem database [ 107 ]. These compounds were analyzed for their binding affinity with NF-κB.…”
Section: Curcumin Target Proteins In Cancermentioning
confidence: 99%
“…On the other hand, curcumin, unlike tetrahydrocurcumin, can directly interact with the STAT3 SH2 domain, suppress its dimerization and subsequent nuclear translocalization [215]. In the case of curcumin sulfate and glucuronide curcumin, their possible inhibitory effects against EGFR and NF-KB cannot be excluded [216] Nevertheless, glucuronide curcumin could have significantly lower cellular uptake compared to natural curcumin. Jamil et al reported, that MDBA-231 human breast cancer cells can metabolize curcumin to curcumin sulphate and subsequently excrete it from the cells [217].…”
Section: Oral Administrationmentioning
confidence: 99%